1995
DOI: 10.1007/bf02208669
|View full text |Cite
|
Sign up to set email alerts
|

β1-Antitrypsin deficiency and chronic pancreatitis

Abstract: Alpha 1-antitrypsin deficiency is a genetic disorder commonly associated with pulmonary and hepatic injury. Low serum levels of this glycoprotein result in an imbalance between circulating protease and protease inhibitors, which is thought to play a role in the development of emphysema. In recent studies, a protease-to-protease inhibitor imbalance in patients with alpha 1-antitrypsin deficiency was thought to be a mechanism contributing to the development of chronic pancreatitis. The heterozygous phenotype and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Although other disease associations have been suggested, they are less well established (99), including glomerulonephritis (100); celiac disease (101); lung, colorectal, and bladder cancers (102); intracranial and intraabdominal aneurysms (103); fibromuscular dysplasia (104); and pancreatitis (105).…”
Section: Clinical Manifestations and Diagnosismentioning
confidence: 99%
“…Although other disease associations have been suggested, they are less well established (99), including glomerulonephritis (100); celiac disease (101); lung, colorectal, and bladder cancers (102); intracranial and intraabdominal aneurysms (103); fibromuscular dysplasia (104); and pancreatitis (105).…”
Section: Clinical Manifestations and Diagnosismentioning
confidence: 99%
“…An association between AAT deficiency and pancreatitis has been the subject of some case reports and case-control studies, [41][42][43] but other studies have found no difference in AAT phenotype in patients with pancreatitis compared with controls. 44 Witt et al recently found no difference in allele frequency between a group of patients with chronic pancreatitis and control subjects.…”
Section: Pancreatitismentioning
confidence: 99%
“…Thus, the low serum activity of this glycoprotein results in an imbalance between circulating proteases as aggressive enzymes are thought to play a role in the development of chronic pancreatitis. [18] Studies by Haber et al ., (1991), have also shown that mortality of experimental pancreatitis is increased with reduced concentrations of circulating α-1AT. [19] The decrease in the antiprotease may result in the activation of proteases that release into the blood stream leading to membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…Some findings indicated increased prevalence of PiS and PiZ in chronic alcoholic patients, while others indicated no difference. [182223] Serum α-1AT concentrations were greater in patients with pancreatitis who were sampled shortly after an acute attack of pancreatitis compared to pancreatitis patients sampled at other times, or to alcoholic controls. [19] Increased α-1AT concentration was found in pancreatic juice of patients with chronic pancreatitis by Miszczuk-Jamska et al .…”
Section: Discussionmentioning
confidence: 99%